Teacher Performance Model In Pandemic Times Based on Emotional Intelligence Mediated And Moderated By Transformational Leadership (Study of Jabodetabek Teacher) - Dellia Mila Vernia (Madani: Jurnal Ilmiah Multidisiplin, 2022)
The examine proposes and tests performance research models influenced by emotional intelligence as well as mediated and moderated by transformational leadership. Coronavirus that has a global impact, very influential to the world of education. Especially in Indonesia, covid19 greatly affects the teaching and learning process, students learn with online systems, they learn from home, these conditions make teachers have to make sure the students understand the learning obtained. In addition, the emotional intelligence condition of teachers is also expected to play a role in maintaining work life balance between work and family. This study evaluated the relationship of the model using PLS through modelling of SEM structural equations through questionnaires given to 211 Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) teachers. The effects of the information analysis showed that emotional intelligence had a advantageous effect on teacher performance. The analysis indicated that emotional intelligence comprise a positive effect on transformational leadership. Information analysis shows that transformational leadership has no positive impact on performance. The information analysis showed that emotional intelligence had no a critical effect on the performance moderated by transformational leadership. Analysis the information revealed that emotional intelligence had no a significant effect on the performance moderated by transformational leadership. This study can be useful to enrich the scientific insights of management, especially related to the application and development of performance concepts.